Ćwiczenia interakcji w dialogu jako metoda terapii logopedycznej (na przykładzie wybranych zaburzeń mowy) (Conversatoria Linguistica, 2019)
The forming process of interactive abilities enables to understand relationships withina social group and to achieve intentions of a speaker. Knowledge about mental and socialdevelopment of a person can be gained from the structure and process of a dialogue. A dialogue,as a form of the speech therapy, should take account of: different interactive grounds, rules ofcommunication and the intention of an utterance. The function of questions is also important ina conscious usage of a dialogue in the speech therapy. The purpose of this article is to raiseawareness that the improvement of both social and communicative competences is possible,despite speech disorders.